Engineers & electrons : - Ryder, John D. (IEEE Press, 1984)
This book introduce in the beginning, discovery and invention, from electricians to engineers, maxwell's prophecy fulfilled. The electron sings a golden tune. The electron shows its muscle. Electrons and holes...